Impacts of burning on soil trace gas fluxes in two wooded savanna sites in Burkina Faso. (June 2019) - van Straaten, Oliver; Doamba, Sabine W.M.F.; Corre, Marife D.; Veldkamp, Edzo
Abstract: In this study, we report the impacts woodland savanna burning has on the soil trace gas fluxes in seasonally dry woodland savannas in Burkina Faso. We measured nitrous oxide (N2 O), nitric oxide (NO), carbon dioxide (CO2 ) and methane (CH4 ) fluxes at two ongoing long-term experimental sites (Tiogo and Dindéresso), each included three fire-exclusion plots and four annually burnt plots (0.24–0.25 ha plot size). We measured soil trace gas fluxes using chamber methods before and after fire during the dry season and at the start of and during the wet season. There was considerable volatilization of aboveground biomass C and N during fire, but soil N2 O, NO, CO2 and CH4 fluxes were not significantly influenced following fire events. Instead, soil moisture dynamics were more important in regulating soil CO2 and N2 O emissions. The onset of the wet season induced a short-term pulse of N2 O emissions, when water-filled pore space exceeded 60%. We also detected a short-term pulse of NO emissions, lasting only four hours, following fire. The low soil N-oxide fluxes reflected the sites' extremely low inorganic N levels in the soil. Highlights: Soil N2 O, CO2 and CH4 fluxes were not significantly influenced by fire events. Short-term NO pulse measured immediately after fire lasting only four hours. First rains after dry season induced a short-term flush of N2 O emissions from soil. Low soil N-oxide fluxes reflect very low inorganic N levels in the soil.